New fears for food old foes, a new threat - Friedman, Gayle; Gausha, Jochi; Cambridge Educational (Firm) (Monmouth Jct., NJ : Cambridge Educational, 2004)
These videoes explains the risks and possible remedies in a lively yet level headed away, to help student replace their fears with fact. Two titles which is irridiation - promise or threat? and old foes, a new threat
vol. 1. Old foes, a new threat vol.2. Irrodiation-promise or threat?
Director, producer, writer, Gayale Frieman ; editor, Jochi Gousha
Host : Gayle Frieman
VHS.
Keywords: Radiation preservation of food; Food contamination; Food Contamination -- prevention and control; Food handling